Innovations and trends in the coconut agroindustry supply chain: A technological surveillance and foresight analysis - Grass Ramírez, José Fernando; Muñoz, Ricardo Camacho; Zartha Sossa, Jhon Wilder (Frontiers in Sustainable Food Systems, 2023)
Coconut (Cocos nucifera) is a raw material that has gained particular relevance for agribusiness in recent years. This has come about largely owing to the paradigm shift regarding its genuine nutritional benefits. It is especially due to innovation that has been incorporated into agro-industrial processing and the development of new products, and the fruits of such labor can be seen in the growing demand by consumers around the world. Integrally making full use of coconut, it turns out, is extremely important for agribusiness. Coconut indeed has become a benchmark, not only from the environmental dimension but also from the social and economic perspectives both of the communities that plant it and the agribusinesses that transform it. This study aims to identify technologies, new uses, trends, and innovations related to the coconut agro-industrial chain, as well as their prioritization, by means of a prospective study, using the Delphi method in two rounds. Two methods applied at the methodological level comprised a technological surveillance study by means of a literature review in a SCOPUS database, PatentsInspiration, complemented with commercial surveillance for the four major topics of plastic wood, coconut oil extraction, high salinity and moisture, and small-scale coconut by-products. Moreover, the Delphi method was used, in two rounds, with 178 topics, technologies, and innovations, classified into seven thematic groups. The Delphi was answered by 32 experts in the two rounds. Vantage Point text mining software was also applied for the analysis of the surveillance results. Within the seven thematic groups, the following 10 priority technologies are highlighted: functional phytochemicals, non-caloric sweeteners, coconut milk preservation technologies, water activity and shelf life, coconut sugar extraction methods, batch and continuous drying technologies, lyophilization, coconut fiber and shredded recycled PET, magnetic particle modification of activated carbon derived from coconut shell and biochar to effectively remove phenol from water, and biodegradable packaging for coconut derivatives. In addition, the following topics were prioritized in the sustainability grouper: sustainable agriculture, bioeconomy, family agriculture, and circular economy.